Rule of law and the catholic social doctrine. An outline of issue - Boike, Paweł (Studia Iuridica Toruniensia, 2021)
First, the author briefly describes the historical development of the idea of supremacy of law. Then he goes on to describe the assessment with which this category of social philosophy was met by the Teaching Office of the Church in the nineteenth and twentieth centuries. Reluctance gives way to acceptance with John XXIII’s Encyclical Pacem in Terris and two documents of the Second Vatican Council: Declaration Dignitatis Humanae andConstitution Gaudium et spes. The Church supports respect for the rule of law, but does not understand it in a positivist way. In the opinion of the Magisterium, formal aspects of the rule of law should be understood as guarantees protecting the inherent rights of the human person.